Reliability of different methods of determining individual inter-stroke intervals in sprint kayaking - Schofield, J. M.; Mullineaux, D. R.; Taylor, D.; Willmott, A. P. (ISBS Proceedings Archive (Michigan), 2018)
The purpose of this study was to explore the reliability of methods for rapidly determining inter-stroke intervals (ISI) of individual kayakers. One participant performed two 150 m trials at a rate of 80 single-strokes/min. ISI were calculated using two criterion measures, visual identification of blade immersion from video record (VID) and peaks in longitudinal acceleration of the kayak hull derrived from a kayak mounted accelerometer (ACC). These measures were compared to ISI from peak footrest force (FRP), initiation of footrest force from a fixed load cell (FRT), paddle Y axis rotational velocity (PAP) and paddle X axis acceleration via an IMU (PAA). Least products regression analysis (LPR) revealed that FRP showed the highest reliability, with no fixed or proportional bias compared to VID or ACC. High ISI during the initial strokes influenced the results of the LPR. A framework for investigating the reliability of ISI using LPR is suggested where the initial strokes are removed prior to analysis.